PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAPKINERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABELINTERVENING(STUDI KASUS PADA PT. GEARINDO PRAKARSA SURABAYA) - YULIA PUTRI, YUNI (Jurnal Ilmu Manajemen (JIM), 2017)
In an organization requires human resources in order to achieve company goals, for it hence required good performance from employees, good performance of course Supported by other factors such as leadership style and work discipline. PT Gearindo Prakarsa Surabaya implements a transformational leadership style. The purpose of this research is to test and analyze the influence of transformational leadership style on employee performance through work discipline. The sample used in the study amounted to 56 employees of PT Gearindo Prakarsa Surabaya. Analytical technique used is Structural Equation Model Partial Least Square with the help of SmartPLS software.The results of this study indicate that the transformational leadership style has a significant effect on work discipline, transformational leadership style has no significant effect on employee performance, work discipline has significant effect on employee performance, and leadership style significantly influence employee performance through work discipline. Keywords: Transformational Leadership Style, Work Discipline, Employee Performance<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />